The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jcv.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Diverse sapovirus genotypes identified in children hospitalised with gastroenteritis in selected regions of South Africa

Abstract: Background: Sapoviruses (SaVs) are recognised as causative agents of gastroenteritis worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 38 publications
(63 reference statements)
4
30
0
Order By: Relevance
“…SaV often showed high genetic diversity during its surveillance, and three of the four human SaV genogroups were detected in this study. During a SaV surveillance in South Africa, a total of 14 genotypes were discovered, including all four human genogroups . Although no SaV genotype has always been prevalent as a predominant genotype in the human population like GII.4 noroviruses, GI.1 and GI.2 are the most reported SaV genotypes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SaV often showed high genetic diversity during its surveillance, and three of the four human SaV genogroups were detected in this study. During a SaV surveillance in South Africa, a total of 14 genotypes were discovered, including all four human genogroups . Although no SaV genotype has always been prevalent as a predominant genotype in the human population like GII.4 noroviruses, GI.1 and GI.2 are the most reported SaV genotypes .…”
Section: Discussionmentioning
confidence: 99%
“…GIV has only a single genotype GIV.1, and GV could be subdivided into two genotypes; GV.1 and GV.2 . A series of studies revealed high genetic diversity of human SaVs in patients suffering from acute gastroenteritis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of NoVs and SaVs as causative agents of gastroenteritis and their diversity in Africa is not well studied, except in some reports from a few African countries [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. There has been only one published study from Ethiopia regarding the presence and genetic diversity of NoVs [37], and none for SaVs to date.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, genotype GII.1 presents a high prevalence compared to other SaV genotypes. 34,35 . The first description of genotype GI.7 was made by analyzing all capsid proteins using universal primers for specific genogroups detected in samples from three prefectures (Chiba, Ehime, and Ishikawa) in Japan between 1999 and 2005 17 .…”
Section: Discussionmentioning
confidence: 99%